The Relationship Between Students’ Speech Anxiety and Perception of Speaking Performance in the English Class - Salainti, Engelina; Sumajouw, Kevin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The study aims to explore the relationship between students' anxiety and perception of speaking performance in English class. Moreover, the research aimed to discover students' anxiety levels and perception of speaking performance in the English class. 57 students (male and female) were selected in the following way using convenience sampling. The students selected a 5-point Likert scale to answer two questionnaires from Horwitz et al. (1986), which was adapted from Nilsson (2019); and Asakereh and Dehghannezha (2015), which was adapted from Rahimi and Abedini (2009). According to the study's findings, students' anxiety and perception of their speaking performance in English classes are negatively related. Thus, it may be said that students’ performance in speaking English was negatively related to their anxiety.